utilization Utilization of tarum leaves as an aesthetic tool in making kajang sarongs: pemanfaatan daun tarum sebagai sarana estetika dalam pembuatan sarung kajang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the use of indigo leaves (daun tarum) as an aesthetic medium and to assess the quality of Kajang sarongs dyed with this natural colorant. Indigo leaves have long been used by the Kajang indigenous community as the main dye for traditional black sarongs, serving as an important part of cultural expression and the identity of the Ammatoa people. This research employs a qualitative approach with observation techniques, in-depth interviews, and documentation. The findings indicate that indigo leaves function not only as a dye but also contain deep aesthetic, symbolic, and philosophical values. The dark blue color produced through a natural fermentation process offers a visual experience that is both subtle and strong, and it possesses high durability. The color also reflects the values of simplicity, purity, and spiritual balance within the Kajang community. Thus, the Kajang sarong represents an aesthetic expression that unites elements of nature, humanity, and culture.